2021
DOI: 10.3389/fmed.2021.753620
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Nurse-Led, Goal-Directed Lung Physiotherapy for Older Patients With Sepsis and Pneumonia in the ICU

Abstract: Objectives: This study aimed to investigate the effect of nurse-led, goal-directed lung physiotherapy (GDLPT) on the prognosis of older patients with sepsis caused by pneumonia in the intensive care unit.Methods: We conducted a prospective, two-phase (before-and-after) study over 3 years called the GDLPT study. All patients received standard lung therapy for sepsis caused by pneumonia and patients in phase 2 also received GDLPT. In this study, 253 older patients (age ≥ 65 years) with sepsis and pneumonia were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…On the basis of our previous studies, 17,18 we also improved our lung physiotherapy strategy. In this study, we not only promoted sputum drainage through early mobilization, vibration, and postural drainage but also ensured adequate humidification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of our previous studies, 17,18 we also improved our lung physiotherapy strategy. In this study, we not only promoted sputum drainage through early mobilization, vibration, and postural drainage but also ensured adequate humidification.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed protocols for lung physiotherapy are given in our previous studies. 17,18 The improved nursing strategy, including an IPC strategy and lung physiotherapy strategy, was as follows (Figure 1).…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that delirium was a frequent complication in older ICU patients, which was similar to previous studies ( Tafelmeier et al, 2019 ; Eertmans et al, 2020 ). Aging is an inevitable trend worldwide ( Sun et al, 2021 ), and could cause an increase in IL-6 and TNF-α in the CNS and peripheral bloodstream even in the absence of disease ( Krabbe et al, 2004 ). The aged brain is more fragile to neuroinflammation because of cellular senescence resulting from senescence-associated secretory phenotype and immunosenescence ( Guerrero et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses play a critical role in managing pulmonary function and should be involved in the implementation and monitoring of chest physiotherapy as a respiratory therapy intervention. 21 This current study aimed to examine the effect of ICPT on pulmonary function and arterial blood gas readings among extubated patients in critical care units. The findings of this current study could potentially contribute to the existing literature and provide valuable insights into the effectiveness of chest physiotherapy as a respiratory therapy intervention.…”
Section: Introductionmentioning
confidence: 99%